P94 Should Adrenaline Auto-Injectors Be Prescribed For Cystic Fibrosis Patients Having Home Intravenous Antibiotics? - A UK National Audit. (19th November 2012) - Fernandes, BN; Jones, A; Simpson, A; Webb, K; Custovic, A
Abstract : Introduction: The UK Cystic Fibrosis (CF) Trust antibiotic guidelines recommends that all patients having home intravenous antibiotics (HIVA) should have an "anaphylactic kit" at home. However, the practise of prescribing adrenaline auto-injectors (AAI) for patients having HIVA varies widely across the country. Studies on HIVA have shown that they are safe, especially if first dose is given in hospital. The aim of this audit is to assess compliance with CF Trust antibiotic guidelines and discover how many patients have experienced anaphylaxis at home while on HIVA. Methods: The audit was performed online from April to September 2011 by asking respondents to fill in a web-based questionnaire. An email was sent to 59 adult and paediatric UK CF centre leads requesting them to take part in this audit. Results: 55/59 (93%) took part in the audit. 16 (29%) routinely prescribe AAI whereas others do not or only prescribe in patients with previous history of allergic reactions to antibiotics (Figure 1 ). 5 physicians reported they knew patients who had experienced anaphylaxis at home. These physicians reported a total of at least 10 anaphylaxis episodes in the last 5 years. 1 mentioned they occurred after the 1st dose, 3 after the 3rd dose and 2 were unsure. 3 reported these patients used their AAI and 3 did not. We estimate that if the average annual number of HIVA courses is 100 courses per centre, this equates to approximately 1 anaphylaxis episode per 2, 700 courses of HIVA. Conclusions: Most CF centres do not routinely prescribe AAI, in contrast to the guidelines issued by the CF trust. Anaphylactic reactions do occur in CF patients having HIVA but this is a relatively rare event. However, as this is a retrospective study based on recall of previous events, the precise nature of the reported reactions cannot be confirmed, so the true prevalence of anaphylactic reactions related to HIVA cannot be ascertained. A prospective multicentre study recording reactions to HIVA and evaluating them in detail (preferably by an allergist) is required.